2018
DOI: 10.1080/08039410.2018.1427624
|View full text |Cite
|
Sign up to set email alerts
|

Public Servants as Development Brokers: The Shaping of INGOs’ Reducing Teenage Pregnancy Projects in Malawi’s Primary Education Sector

Abstract: International non-governmental organisations (INGOs) play an increasingly prominent and multifaceted role in the field of global healthas policy advocates, recipients of donor funds, and implementers of donor-funded programmes. Many such NGOs and their local affiliates have become highly professionalized and oriented towards the priorities of global-level actors, with potential negative consequences for their ability to represent the grassroots and to challenge structures of power and inequality. In this thesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…This draws parallels with research on "street-level bureaucrats", who manage policy implementation and "broker" project demands in the context of resource constraints. 45,46 Local actors' inability to hold powerful actors to account demonstrates that webs of accountability are uneven. Only when we analyse power relations from the global to the local level, and how these dynamically interact with policies, can we understand how inequities are shaped.…”
Section: Resultsmentioning
confidence: 99%
“…This draws parallels with research on "street-level bureaucrats", who manage policy implementation and "broker" project demands in the context of resource constraints. 45,46 Local actors' inability to hold powerful actors to account demonstrates that webs of accountability are uneven. Only when we analyse power relations from the global to the local level, and how these dynamically interact with policies, can we understand how inequities are shaped.…”
Section: Resultsmentioning
confidence: 99%
“…There is no unidirectional way of implementing a new policy. Instead, enactment is an ongoing process of reflection, interpretation, and mediation in which teachers play central roles (Altinyelken 2011b;Ball, Maguire, and Braun 2012;Pot 2018). Future education policies and programmes should thus pay attention to ways to strengthen teachers' positions in and outside schools, and reflexivity in teacher professional development.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the international development actors in schools has also had its effect on teachers; Pot (2018) describes how teachers in Malawi act as 'development brokers', advocating messages from non-governmental organisations (NGOs) to wider communities. Pot (2018) revealed that selected teachers became important resources for NGOs, and enjoy a relatively higher social status in their communities due to their affiliation to international organisations. At the same time, such association with development or the 'cosmopolitan' may also lead to teachers feeling alienated from their communities (Barrett 2005).…”
Section: Teacher Enactment and Policy Re-contextualisationmentioning
confidence: 99%
“…Due to RTP's multi-sectoral approach and focus on behaviour change, it was better than other efforts aimed at reducing teenage pregnancies. Such analysis, it can also be argued, helped to legitimise the need for this specific project in a situation of many other projects addressing teenage pregnancies (Pot 2019b). In particular, it was necessary to address environmental (family, friends and institutions) and individual (risk perception, vulnerability and opportunity) barriers for the use of youth-friendly health services, with an emphasis on sociocultural factors (Save the Children Norway 2013, 5).…”
Section: Methodsmentioning
confidence: 99%
“…Further, these girls often made appearances during donor visits as testimonies of success, telling their story about how the project had helped them back to school. Although success was attributed to this specific NGO project, Pot (2019b) has shown how such testimonies and the attribution given are not always clear in a context where multiple NGOs have been implementing similar projects. Common to these testimonies was a linear cause-effect chain in line with the global discourse: the girls had dropped out due to pregnancies and were not aware of the readmission policy until project partners informed them and helped them back to school.…”
Section: Demonstrating Success On the Groundmentioning
confidence: 95%